2018
DOI: 10.1016/j.bbamcr.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Different phosphorylation patterns regulate α1D-adrenoceptor signaling and desensitization

Abstract: Human α-adrenoceptors (α-ARs) are a group of the seven transmembrane-spanning proteins that mediate many of the physiological and pathophysiological actions of adrenaline and noradrenaline. Although it is known that α-ARs are phosphoproteins, their specific phosphorylation sites and the kinases involved in their phosphorylation remain largely unknown. Using a combination of in silico analysis, mass spectrometry and site directed mutagenesis, we identified distinct α-AR phosphorylation patterns during noradrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 69 publications
2
29
0
Order By: Relevance
“…Schematic representation of the substrates for phosphorylation currently identified in the three human α 1 ‐adrenoceptors (AR) subtypes (large red, yellow, and blue circles). Phosphorylated residues in the α 1A ‐ and α 1D ‐ adrenoceptors were identified by MS (Alcantara‐Hernandez et al, ; Alfonzo‐Méndez et al, ), whereas for the α 1B ‐adrenoceptor, the residues were identified by site‐directed mutagenesis and functional analysis of the hamster orthologue (Diviani et al, ; in parenthesis are the sites defined for the hamster receptor). Below the diagram are the sequence alignments of the third intracellular loop and the carboxyl terminus (C‐tail) of the three human α 1 ‐adrenoceptor subtypes.…”
Section: Regulation Of α1‐adrenoceptors By Phosphorylationmentioning
confidence: 99%
See 4 more Smart Citations
“…Schematic representation of the substrates for phosphorylation currently identified in the three human α 1 ‐adrenoceptors (AR) subtypes (large red, yellow, and blue circles). Phosphorylated residues in the α 1A ‐ and α 1D ‐ adrenoceptors were identified by MS (Alcantara‐Hernandez et al, ; Alfonzo‐Méndez et al, ), whereas for the α 1B ‐adrenoceptor, the residues were identified by site‐directed mutagenesis and functional analysis of the hamster orthologue (Diviani et al, ; in parenthesis are the sites defined for the hamster receptor). Below the diagram are the sequence alignments of the third intracellular loop and the carboxyl terminus (C‐tail) of the three human α 1 ‐adrenoceptor subtypes.…”
Section: Regulation Of α1‐adrenoceptors By Phosphorylationmentioning
confidence: 99%
“…The phosphorylation sites of α 1A ‐ and α 1D ‐adrenoceptors were only recently identifed (Alcantara‐Hernandez et al, ;Alfonzo‐Méndez et al, ;Carmona‐Rosas et al, ). These adrenoceptors are phosphorylated in both the third intracellular loop and C‐tail.…”
Section: Regulation Of α1‐adrenoceptors By Phosphorylationmentioning
confidence: 99%
See 3 more Smart Citations